Exploring Gender Dynamics in Sustainable Ecotourism: A Gender Perspective Review of Social Change and Livelihood Strategies Among the Tengger Tribe in Probolinggo District - Nurul Novikarumsari; Desy Fitria Wulansari; Rokhani; Sofia; Rindi Metalisa (Universitas Muhammadiyah Malang, 2024)
Probolinggo Regency in East Java presents notable tourist destinations and holds significant potential for sustainable ecotourism endeavors. Mount Bromo stands out as a prime natural attraction in this region of Indonesia, drawing both domestic and international visitors. The indigenous Tengger tribe inhabits the area surrounding Mount Bromo. With the goal of bolstering tourism, both locally and internationally, the Probolinggo Government has actively developed Mount Bromo's natural allure. This study aims to: 1) analyze the gender dynamics within horticultural farmer households in Ngadisari, Probolinggo, and 2) elucidate the catalysts and impediments to socioeconomic transformation within the Tengger tribe's engagement in ecotourism-related economic activities. Employing a qualitative approach with a gender perspective, this research deliberately selected Ngadisari, a village in Probolinggo, due to its pivotal role in supporting Mount Bromo's tourism and its predominantly Tengger population. Furthermore, Ngadisari has been earmarked by the Probolinggo authorities as a tourism-centric village. Data analysis entailed descriptive qualitative and gender analyses, with the aim of fostering the development of a gender-equitable, community-driven empowerment model.